Understanding accountability : new perspectives on a fractured world - Flinders, Matthew; Dimova, Gergana; Monaghan, Christopher (Routledge, 2026)
This book brings clarity and understanding to the concept of accountability through the lens of conceptual political analysis. As the structure of the modern state has become more complex, the architecture of accountability has itself needed to evolve and re-orientate in an attempt to keep pace. This has led to an increased emphasis not on accountability per se but on different kinds or types of accountability. As such, it is argued here that accountability has emerged to become a concept with adjectives and there is a real need to properly understand accountability in an increasingly fractured world. The theoretical and analytical glue that binds all of the chapters in this collection is a commitment to working within the contours of the work of the philosopher, Giovanni Sartori. This is an approach that has been used to tease apart and interrogate a range of concepts including terrorism, governance, coups, gender equality, deliberation, warfare, clientelism, hybrid regimes, democracy, right through to art, love, rape and violence. It is also an approach that facilitates the cultivation of complex debates concerning the limits of conceptual flexibility. The volume consists of twelve chapters, grouped into three main parts. The introductory part provides the foundations for the collection. Part I on Power explores the normative dimensions of accountability as a means to control and regulate power. Part II on Politics focuses inter alia on accountability following a period of crisis and the emergence of new technology such as algorithms. The final part, Part III, on Particularities looks at concepts such as social accountability and what is meant by supplementary accountability. This broad-ranging collection increases the conceptual toolkit that social and political scientists and lawyers can use to interrogate change at a number of levels and in a range of sectors. Whether through a focus on moral, individual or gendered accountability, or through a shift towards clashing, stakeholder or social accountability, there is a clear flow and coherence through the chapters. The volume will be of interest to academics and researchers working in the areas of Legal and Political Theory, Legal and Political Philosophy and Accountability Studies.
Keywords: Government liability.; Judicial independence.; Judicial power.; Liability (Law) -- Political aspects.; Liability (Law); Responsibility.; elektronické knihy; electronic books